THE CONCEPTUAL THOUGHTS AND IDEAS, REFORMS, THEIR ESSENCE AND SIGNIFICANCE IN UZBEKISTAN EXPRESSED IN THE ADDRESS OF THE PRESIDENT OF THE REPUBLIC OF UZBEKISTAN SHAVKAT MIRZIYOEV TO THE OLIY MAJLIS AND THE PEOPLE OF UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2023)
In the article, the conceptual thoughts and ideas, reforms, their nature and importance in Uzbekistan, which were stated in the address of the President of the Republic of Uzbekistan Shavkat Mirziyoev to the Oliy Majlis and the people of Uzbekistan, are analyzed in detail with the help of information from scientific literature.